Teacher Support And Peer Influence As Determinants Of Reproductive Hygiene Practices Among Islamic Boarding School Students In West Lombok, Indonesia - Karjono, M; Ningsih, Murtiana; Mulyaningsih, Misroh (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2025)
Background: Maintaining reproductive hygiene, particularly external reproductive organ cleanliness among female students in Islamic boarding schools, is a crucial aspect of personal hygiene that requires special attention in daily life.Objective: This study aimed to analyze the relationship between information sources, teacher support, and peer influence with reproductive hygiene practices among female students at al Ishlahuddiny Islamic Boarding School, West Lombok, Indonesia.Method: This study employed an analytical observational design with a cross-sectional approach. The study population consisted of 186 female students, and a total of 65 respondents were selected using a systematic random sampling technique. Independent variables included information sources, teacher support, and peer influence, while the dependent variable was reproductive hygiene practices. Data were analyzed through univariate and bivariate analyses using computer-assisted statistical software.Results: More than half of the respondents had access to information sources (53.8%), received teacher support (56.9%), and experienced peer influence (61%), while 63.1% demonstrated good reproductive hygiene practices. There was a significant relationship between teacher support (p=0.016; r=0.76) and peer influence (p=0.003; r=0.82) with reproductive hygiene practices. However, information sources (p=0.113) showed there was not any significant relationship.Conclusion: Teacher support and peer influence were significantly relationship with reproductive hygiene practices among female students in Islamic boarding schools. Strengthening the role of teachers as mentors, along with improving students’ knowledge and skills in maintaining reproductive hygiene, is recommended to promote better reproductive health outcomes.